1991
DOI: 10.1007/bf01796842
|View full text |Cite
|
Sign up to set email alerts
|

The choice between a married or unmarried first union by young adults

Abstract: Liefbroer, A.C., 1991, The choice between a married or unmarried first union by young adults: A competing risks analysis, European Journal of Population 7, In this paper the choice between marriage and unmarried cohabitation as a first union by young adults is studied. A hazard analysis is performed on a sample of 590 26-year-old men and women from the Netherlands. Students are much less likely to start a union in general, and marriage in particular, than are other categories of young adults. Young adults livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
0
46
0
2
Order By: Relevance
“…Starting with background characteristics, we find that the parents' religiosity has no effect on union formation. It does have a very clear effect on the type of entry, however, with men from more religious backgrounds being less likely to cohabit and more likely to marry directly, as earlier studies have indicated (Liefbroer 1991;Thornton et al 1992). It is interesting that religiosity has no effect on the transition to marriage that follows a period of cohabitation.…”
Section: Effects Of Employment On Union Transitionsmentioning
confidence: 88%
See 2 more Smart Citations
“…Starting with background characteristics, we find that the parents' religiosity has no effect on union formation. It does have a very clear effect on the type of entry, however, with men from more religious backgrounds being less likely to cohabit and more likely to marry directly, as earlier studies have indicated (Liefbroer 1991;Thornton et al 1992). It is interesting that religiosity has no effect on the transition to marriage that follows a period of cohabitation.…”
Section: Effects Of Employment On Union Transitionsmentioning
confidence: 88%
“…Cohabitation can therefore be used as a way for couples to reduce uncertainty, before marriage, about future career prospects. Recent American evidence does suggest that economic prospects are less important for entry into cohabitation, although it is less clear whether favourable economic prospects among men also have a positive effect on the transition from cohabitation to marriage (Liefbroer 1991;Smock and Manning 1997;Bracher and Santow 1998;Kravdal 1999;Brown 2000;Oppenheimer 2003;Sassler and McNally 2003;Xie et al 2003).…”
Section: Hypotheses About the Effects Of Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Liefbroer et al (1994) found a lower rate of union formation for those living independently than for those living with their parents (note that their study only included young people who had a steady dating relationship with someone from the opposite sex). Liefbroer (1991) found no significant effect on union formation, but a positive effect on unmarried cohabitation and a negative effect on marriage. For Britain, Berrington and Diamond (2000) found a strong positive effect on cohabitation for both men and women, a smaller negative effect on marriage for women, and hardly any effect on marriage for men.…”
Section: Formationmentioning
confidence: 73%
“…On the one hand, level of education indicates income potential and would thus lead to earlier union formation (compare Oppenheimer, 1988). On the other hand, high education has been argued to indicate a degree of non-traditionality (Liefbroer, 1991;Manting, 1994), which would lead to later union formation (and particularly later marriage). For the Netherlands and Flanders, Liefbroer and Corijn (1999) found a small delaying impact of educational attainment on union formation.…”
Section: Individual Resources and First Union Formationmentioning
confidence: 99%